Trace Metals Distribution in Sediment Fractions of Karimata Strait, Indonesia - Duaitd Kolibongso; Tri Prartono; Ali Arman (Marine Science Department Diponegoro University, 2017)
The profile concentration of heavy metals, organic matter and the composition of the grain sizes is determined in two sediment cores from Karimata Strait. This study aimed to estimate the distribution of sediment grain sizes and distribution of heavy metals (Pb, Cu, Zn, Ni, As, and Fe) in three sediment fractions (>250 μm, 63-250 μm and <63 m) of Karimata Strait. Sampling was conducted using box core. Graining size analysis was carried out through sieving, continue with digestion, and analyze the heavy metals using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Results of the study show that the sediment grain size distribution is strongly influenced by the water hydrodynamic condition (currents). It can be seen by the dominance of finding coarse grain size in the research areas. The highest concentration of the heavy metals was found in the finest grain size (<63 m) due to the larger surface area and higher adsorption capacity. Distribution of heavy metals Cu, Pb, Zn and Ni in the upper layer of sediments is higher than in the bottom layer. Furthermore, the As and Fe concentration in the surface were lower than in the bottom layer. Statistical analysis shows an association and a source of heavy metals mainly coming from the surrounding areas. It is supported by the enrichment factor values of finding heavy metals generally has been undergone enrichment.Keyword: Grain sizes,Heavy metals, ICP-OES,Karimata strait, Sediment